Among the righteous : lost stories from the Holocaust's long reach into Arab lands - Satloff, Robert, 1962- 1962- (PublicAffairs, 2006)
Looks at the reaction of the Arab people to the Holocaust in North Africa, where thousands of Jews were forced into labor camps.